2020
DOI: 10.1108/ec-01-2020-0032
|View full text |Cite
|
Sign up to set email alerts
|

Structure optimization of plough blades in a ploughshare mixer using the DEM simulations

Abstract: Purpose The purpose of this paper is to optimize the structure of plough blades in a ploughshare mixer using the discrete element method (DEM) simulations. Design/methodology/approach Using the validated DEM model, three numerical tests are conducted to determine how the mixing performance evolves as structural parameters of blades change. Results from the analysis provide basis for structure optimization of blades. The structural parameters include sweep angle of blade γ, regular axial pitch p and regular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In this paper, the circumferential distribution angle between adjacent ploughshares is assumed same, which benefits the standardization of design and manufacture. Although Fang Z [9] found that opposite distribution clamping 180 for ploughshares is possibly more conducive to the mixing performance, the ploughshares inserted into materials at the same time may suffer from greater resistance and wear. Therefore, it is worth studying the appropriate distribution angle.…”
Section: Parameters To Be Studiedmentioning
confidence: 99%
“…In this paper, the circumferential distribution angle between adjacent ploughshares is assumed same, which benefits the standardization of design and manufacture. Although Fang Z [9] found that opposite distribution clamping 180 for ploughshares is possibly more conducive to the mixing performance, the ploughshares inserted into materials at the same time may suffer from greater resistance and wear. Therefore, it is worth studying the appropriate distribution angle.…”
Section: Parameters To Be Studiedmentioning
confidence: 99%